Alterations in the whole brain network organization after prenatal ethanol exposure. (11th January 2020) - Tang, Shiyu; Xu, Su; Zhu, Wenjun; Gullapalli, Rao P.; Mooney, Sandra M.
Abstract: Background: People with fetal alcohol spectrum disorder (FASD) often have structural or functional alterations of the central nervous system, including changes in brain network organization. These have been associated with neuropsychological deficits, but outcomes are not consistent across studies. We used a rat model of FASD to assess brain network alterations in males and females following ethanol exposure during a prenatal period similar to the first half of gestation in humans. Methods: Pregnant Long Evans rats were given an ethanol‐containing or isocaloric non‐ethanol diet from gestation day 6 to 20. Resting‐state functional magnetic resonance imaging was performed on offspring in young adulthood. Graph theoretical analysis was used to assess properties associated with the whole brain network organization, with a focus on segregation, integration, and small‐world organization—a feature which allows specialized local information processing (segregation) and simultaneously efficient global information sharing (integration). Results: Ethanol‐exposed females showed a significant decrease in small‐worldness compared with control females or with ethanol‐exposed males. Compared to control females, the proportion of animals with atypically high path length (1 standard deviation higher than the grand average) was significantly higher in ethanol‐exposed females, indicating that the alteration in small‐world organization is driven by decreased network integration. No significant effects were seen in males. Conclusion: The results revealed that prenatal ethanol exposure disrupts the balance between network segregation and integration in young adult female rats. The whole brain network is less integrated after ethanol exposure in the females, suggesting wide‐spread reduction of long‐range regional communication. Abstract : In this study, we used a rat model of fetal alcohol spectrum disorders (FASDs) and assessed brain network alterations following ethanol exposure during a prenatal period similar to the first half of gestation in humans. The results revealed that prenatal ethanol exposure disrupts the segregation/integration balance of the brain network and reduced network integration in young adult female rats, suggesting wide‐spread reduction of long‐range regional communication.